2011
DOI: 10.5194/tc-5-617-2011
|View full text |Cite
|
Sign up to set email alerts
|

Variability of snow depth at the plot scale: implications for mean depth estimation and sampling strategies

Abstract: Abstract. Snow depth variability over small distances can affect the representativeness of depth samples taken at the local scale, which are often used to assess the spatial distribution of snow at regional and basin scales. To assess spatial variability at the plot scale, intensive snow depth sampling was conducted during January and April 2009 in 15 plots in the RioÉsera Valley, central Spanish Pyrenees Mountains. Each plot (10 × 10 m; 100 m 2 ) was subdivided into a grid of 1 m 2 squares; sampling at the co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 28 publications
2
74
1
1
Order By: Relevance
“…The range of CV that we have found here is lower than those reported by, e.g., López-Moreno et al (2015), but seems in agreement with the results by López-Moreno et al (2011) for a survey performed during January. Snow depth spatial variability increases with time during the year (Mé-nard et al, 2014;López-Moreno et al, 2015), due to local heterogeneity in ablation dynamics.…”
Section: Test 2: the Effect Of Spatial Sampling On Snow Depth Statisticscontrasting
confidence: 47%
“…The range of CV that we have found here is lower than those reported by, e.g., López-Moreno et al (2015), but seems in agreement with the results by López-Moreno et al (2011) for a survey performed during January. Snow depth spatial variability increases with time during the year (Mé-nard et al, 2014;López-Moreno et al, 2015), due to local heterogeneity in ablation dynamics.…”
Section: Test 2: the Effect Of Spatial Sampling On Snow Depth Statisticscontrasting
confidence: 47%
“…On the other hand, for the same reason sampled transects should represent lengths longer than L ex (López-Moreno et al, 2011). However, the RMSD analysis of the sample spacing (and thus the sample size) in transects of 200, 100, and 50 m, showed that in most of the land cover groups investigated, less than five samples were adequate to describe the average snow depth with a RMSD error less than 5 %.…”
Section: Discussionmentioning
confidence: 99%
“…When the average of coefficient of variation for each land cover group, representing the whole campaign period, was calculated (Table 4), the dispersion of snow depth was highest over the LR and the B and remained low in the forested land cover groups and over the FM. Coefficient of variation for the same order of magnitude (from 0.12 to 0.22) for different types of sites in a boreal landscape, have been reported by Neumann et al (2006) and for forested test sites by López-Moreno et al (2011).…”
Section: Land Cover Specific Variation Of Snow Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast to this, the role of topography and fine-scale variability of snow cover evolution is investigated in a number of local studies by, e.g. Jost et al (2007), López-Moreno et al (2011), Grünewald et al (2010), and Schmidt et al (2009).…”
Section: Introductionmentioning
confidence: 99%